IMPLEMENTASI PROGRAM BANTUAN STIMULAN PERUMAHAN SWADAYA (BSPS) - Harapan Tua R.F.S, Islaeny Rismanita, Zaili Rusli, (Jurnal Ilmu Administrasi Negara, 2020)
Implementation of the Self-Help Housing Stimulant Assistance Program (BSPS). The purpose of this study was to determine the implementation of the Self-Help Housing Stimulant Assistance Program (BSPS) in Koto Tuo Barat Village District XIII Koto Kampar Kampar Regency. This research is a qualitative descriptive study. Data collection techniques used were interviews, literature study. Data collected in the classification then moves towards the formation of conclusions. The results of the study concluded that the implementation of the Self-Help Housing Stimulant Assistance Program (BSPS) in the Village of Koto Tuo Barat District XIII Koto Kampar Kampar Regency Based on Riau Governor Regulation Number: 12 of 2012 concerning Guidelines for Implementing Development in the Field of Settlements with Community Empowerment Patterns and Regulation of the Minister of Public Works and Housing Rakyat Republik Indonesia Number 07 / PRT / M / 2018 2018 Regarding Self-Help Housing Stimulant Assistance. Starting from the planning stage in the form of organizing Prospective Beneficiaries (CPB), submitting proposals in the form of money, ratification of proposals by the Technical Team, and Proposal Proposal to the Commitment Making Officer (PPK).